A Mixed Methods Research Study of Parental Perception of Physical Activity and Quality of Life of Children Under Home Lock Down in the COVID-19 Pandemic - López-Aymes, Gabriela; Valadez, María de los Dolores; Rodríguez-Naveiras, Elena; Castellanos-Simons, Doris; Aguirre, Triana; Borges, África (Frontiers in Psychology, 2021)
Household confinement due to the rapid spread of the pandemic caused by COVID-19 has brought very significant changes, such as the forced stay-at-home of children due to the closure of schools. This has meant drastic changes in the organization of daily life and restrictions on their activities, including exercise, which could affect the quality of life of the children due to its importance. In order to study the relationship between physical activity and psychological well-being of minors, a study has been carried out with Mixed Methods Research, combining survey methodology with transversal design with qualitative methodology using discourse analysis. 234 parents of minors in Spain and several Spanish-speaking countries in America participated. The instrument was a questionnaire in Google Forms, which included the Kidscreen-27 quality of life scale. The results show significant differences in both the type of physical activity and its frequency due to age, and differences in parents' perception of whether their children’s physical activity levels were sufficient or not, both on the health, mood and school subscales, and in the categorization of open responses referring to concerns due to the pandemic, analyzed with the ALCESTE technique. The relationship between physical activity of children and adolescents and quality of life is clearly concluded.